Jogos e música: Recursos terapêuticos ocupacionais no tratamento de adolescentes usuários de substâncias psicoativas - da Silva, Meire Luci [UNESP]; Rosa, Sambleisse Sodré [UNESP] (My University, 2017)
Objective: This article aims to investigate the effectiveness of music and games as occupational therapeutic resources in the care of psychoactive substance users in treatment, admitted to a psychiatric hospital in the mid-western part of São Paulo state. Method: Study conducted during the Supervised Internship of Occupational Therapy (OT) in Mental Health and Substance abuse at the State University of São Paulo. About 10 teenagers from 9-17 years old participated in the study. For data collection 11 workshops were conducted during three months, lasting one hour, held in the OT area of the hospital. During the workshops music and adapted games were used as resources. Data were recorded on audio and field diary and the data analysis was based on thematic content analysis. Results: The games and music used in occupational therapy service with psychoactive substance teenage users configured as an effective and powerful tool in the treatment. It allowed the approach to issues regarding cognitive aspects, social interaction, expression of feelings, simulations of real life situations, exposure to situations of risks vulnerability, possibilities of choice, among others, in an attractive, playful, fun, expressive and dynamic way. Conclusion: It was possible to verify the importance of specific actions and strategies as potent therapeutic resources for a promising and effective intervention in the treatment of addiction, helping the teenager in the (re) establishment and empowerment of their life.
Games and music: Therapeutic occupational resources in the treatment of teenagers users of psychoactive substances
Keywords: Adolescent; Experimental; Games; Music; Occupational therapy; Substance-related disorders